Human Capital and Per Capita Income in Ecuador - Vayas-Ortega, Germania (2024)
Human capital and per capita income are crucial in Ecuador’s economic development. Human capital, represented by the population’s education, health, and skills, directly influences the productivity and economic growth of the country. In turn, per capita income reflects citizens’ average income level and ability to access goods and services. The data analyzed comes from the World Bank database from 2000 to 2020. The main results indicate significant improvements in human capital due to various education and training strategies that different governments have applied